Acetate Revisited: A Key Biomolecule at the Nexus of Metabolism, Epigenetics and Oncogenesis—Part 1: Acetyl-CoA, Acetogenesis and Acyl-CoA Short-Chain Synthetases - Moffett, John R.; Puthillathu, Narayanan; Vengilote, Ranjini; Jaworski, Diane M.; Namboodiri, Aryan M. (Frontiers in Physiology, 2020)
Acetate is a major end product of bacterial fermentation of fiber in the gut. Acetate, whether derived from the diet or from fermentation in the colon, has been implicated in a range of health benefits. Acetate is also generated in and released from various tissues including the intestine and liver, and is generated within all cells by deacetylation reactions. To be utilized, all acetate, regardless of the source, must be converted to acetyl coenzyme A (acetyl-CoA), which is carried out by enzymes known as acyl-CoA short-chain synthetases. Acyl-CoA short-chain synthetase-2 (ACSS2) is present in the cytosol and nuclei of many cell types, whereas ACSS1 is mitochondrial, with greatest expression in heart, skeletal muscle, and brown adipose tissue. In addition to acting to redistribute carbon systemically like a ketone body, acetate is becoming recognized as a cellular regulatory molecule with diverse functions beyond the formation of acetyl-CoA for energy derivation and lipogenesis. Acetate acts, in part, as a metabolic sensor linking nutrient balance and cellular stress responses with gene transcription and the regulation of protein function. ACSS2 is an important task-switching component of this sensory system wherein nutrient deprivation, hypoxia and other stressors shift ACSS2 from a lipogenic role in the cytoplasm to a regulatory role in the cell nucleus. Protein acetylation is a critical post-translational modification involved in regulating cell behavior, and alterations in protein acetylation status have been linked to multiple disease states, including cancer. Improving our fundamental understanding of the “acetylome” and how acetate is generated and utilized at the subcellular level in different cell types will provide much needed insight into normal and neoplastic cellular metabolism and the epigenetic regulation of phenotypic expression under different physiological stressors.